FEMININE IDENTITY IN REFINED MALE AND FEMALE CHARACTERS OF WAYANG KULIT KELANTAN - Fara Dayana Mohd Jufry, Mohd Kipli Abdul Rahman, Nor Shuradi Nor Hashim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Wayang Kulit Kelantan is one of the traditional theatre performance that holds unique identity. This shadow play performance uses gambalan (shadow puppet) to depict the characters from the Hikayat Seri Rama (a repertoire of Wayang Kulit Kelantan). There are two main characters in Wayang Kulit Kelantan, which are refined characters and rough characters. This research focuses only on the similarity in identity of the refined characters which encompass high percentage of feminine traits. The discussion in this paperwork only focuses on two refined characters which are Seri Rama and Siti Dewi. This discussion is structured based on Gender Schema Theory by Bem, through the application of Bem Sex-Role Inventory as the tool to determine the feminine traits that exist in these refined characters. With the use of this inventory, it is discovered that all three of these characters have high percentage of feminine traits even though from different gender. Therefore this research has made a new discovery through primarily applying western theory in the identification process of refined characters of Wayang Kulit Kelantan.